The Influence Of Price, Trust, And Quality Of Service On The Decision To Use Oriskin Medan Clinic Services - Dewi Nurmasari Pane; Miftah El Fikri; Mustofa (Yayasan Multidimensi Kreatif, 2023)
This study aims to investigate the influence of price, trust, and service quality on decisions to use Oriskin Medan Clinic services. This research is an attempt to understand the factors that influence individual choices in choosing health services at this clinic. Data was collected through a survey involving a sample of Oriskin Medan Clinic patients. The results of this study reveal that price, level of trust in the clinic, and service quality contribute significantly to the decision to use clinic services. These findings highlight the importance of these aspects in influencing patient preferences in choosing a health clinic. Managerial implications and recommendations for healthcare practitioners are also discussed in this study to improve patient experience and sustainability of Oriskin Medan Clinic. This study can provide useful insights for stakeholders in the healthcare industry to develop more effective strategies in maintaining and increasing market share.